Factors influencing nitrification rates and the abundance and transcriptional activity of ammonia‐oxidizing microorganisms in the dark northeast Pacific Ocean. (15th December 2015) - Smith, Jason M.; Damashek, Julian; Chavez, Francisco P.; Francis, Christopher A.
Abstract: Pelagic marine Thaumarchaea play a primary role in ammonia oxidation, an integral part of nitrification and the nitrogen cycle. This study examines how physicochemical and biological variables influence rates of nitrification and the distribution, abundance and activity of ammonia oxidizers throughout the dark northeast Pacific Ocean. Nitrification rates are highest near the epipelagic‐upper mesopelagic transition and decrease with depth according to a Martin‐like power function, suggestive of a coupling to the organic matter flux. In contrast, archaeal and bacterial ammonia monooxygenase ( amoA ) gene abundance remains fairly constant throughout the upper mesopelagic. Density‐based composites reveal nitrification to be highest in the upper pycnocline, within the nitrate:silica and ammonium maxima, while ammonia‐oxidizing archaea (AOA) abundances are highest in the lower pycnocline. Water column group A (WCA) and B (WCB) AOA amoA genes are present throughout the dark ocean but have no relationship to nitrification rates. WCA comprise the majority of the AOA community above 200 m and WCB comprise the majority of it below 500 m, largely because WCA abundances decrease precipitously from 200 m to 500 m. WCA and WCB amoA genes are actively transcribed throughout the dark ocean, irrespective of conditions. Thaumarchaeal urease ( ureC ) genes are also present throughout, implying a widespread capacity for mixotrophy; however, unlike amoA, their expression is not detectable. Together, the results support a strong linkage between organic matter flux and nitrification rates, identify density as an important control over AOA distributions, and suggest that WCA and WCB distributions are influenced by the availability of their preferred substrates in the dark ocean.